2018
DOI: 10.1007/s00345-018-2402-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urodynamic preoperative detrusor overactivity on the outcomes of transurethral surgery in patients with male bladder outlet obstruction: a systematic review and meta-analysis

Abstract: Our meta-analysis results demonstrated that preoperative urodynamic DO has no diagnostic role in the prediction of surgical outcomes in patients with male BOO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Liu et al [ 22 ] and the present findings indicate that preoperative DO is a positive prognostic factor in patients with DU undergoing bladder outlet surgery. In contrast, a recent meta-analysis found no correlation between preoperative DO and surgical outcomes in male patients with BOO [ 23 ]. Moreover, a large-scale study demonstrated that both age and BOO are independently associated with the presence of DO [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 22 ] and the present findings indicate that preoperative DO is a positive prognostic factor in patients with DU undergoing bladder outlet surgery. In contrast, a recent meta-analysis found no correlation between preoperative DO and surgical outcomes in male patients with BOO [ 23 ]. Moreover, a large-scale study demonstrated that both age and BOO are independently associated with the presence of DO [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent meta-analyses have been published by Kim et al in which the authors evaluated the impact of preoperative DUA or DO in LUTS/BPH patients undergoing deobstructive surgery, based on results from comparative studies [29,30]. The authors found that preoperative DUA was significantly associated with poorer degrees of IPSS and Qmax improvements, as well as a poorer tendency (although not statistically significant) toward IPSS-QoL and PVR improvements.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that preoperative DUA was significantly associated with poorer degrees of IPSS and Qmax improvements, as well as a poorer tendency (although not statistically significant) toward IPSS-QoL and PVR improvements. On the other hand, improvements in the total IPSS, IPSS-QoL, Qmax, and PVR were similar between patients with and without preoperative DO [29,30]. Although several studies on the subject have been published, the exact role of DUA and DO before surgical intervention is still to be determined [27,28,[31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is controversial that UDS may not change the management of lower urinary tract symptom (LUTS), it nonetheless plays an important role in prognostication and expectation management before urologic procedures—both important aspects in patients’ perceived effectiveness and impact on quality of life 3 . Furthermore, recent randomized control trials and meta‐analyses demonstrate limited utility in performing UDS for the treatment of BOO, and that performing UDS does not reduce surgery rates 4,5 . Moreover, current guidelines do not recommend UDS in preoperative evaluation for male LUTS, unless there is diagnostic uncertainty 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, recent randomized control trials and meta-analyses demonstrate limited utility in performing UDS for the treatment of BOO, and that performing UDS does not reduce surgery rates. 4,5 Moreover, current guidelines do not recommend UDS in preoperative evaluation for male LUTS, unless there is diagnostic uncertainty. 6,7 Given the controversy surrounding UDS and BPH, we hypothesized that there is significant practice variation and we sought to leverage American Board of Urology (ABU) case log data to evaluate practice patterns to discern factors associated with performing UDS for BPH.…”
Section: Introductionmentioning
confidence: 99%